2011
DOI: 10.1017/s0021911811000088
|View full text |Cite
|
Sign up to set email alerts
|

A Muslim Vision for the Chinese Nation: Chinese Pilgrimage Missions to Mecca during World War II

Abstract: In the late 1930s, three groups of Sino-Muslims went on hajj trips to Mecca. Two of them represented the Republic of China, while one represented the puppet government in Japanese-occupied North China. Reflecting the political importance of the Muslim population in the Sino-Japanese struggle, each group engaged in propaganda efforts for its government. However the Sino-Muslims who participated in these missions were not merely the passive pawns of Chinese authorities. Rather, archival material and published so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…72 The opening of the coastal cities, however, meant that, in parallel to the Chinese "May Fourth" cultural movement (1910)(1911)(1912)(1913)(1914)(1915)(1916)(1917)(1918)(1919)(1920)(1921)(1922)(1923)(1924)(1925), eastern Hui intellectuals were quick to launch their own cultural revival movement. 73 Central to these Hui intellectuals' initiatives was the revival of their depressed Islamic learning and the education of their fellow Muslims in the ideas of modern statehood and scientific knowledge. From the year 1900 on, elite Hui Muslim families had been sending their children to Japan, an effort culminating in the establishment of the Association for Islamic Education in Tokyo (留東清真教育總會 Liudong qingzhen jiaoyu zonghui) in June 1907.…”
Section: Homogenizing Drives Of Eastern Hui: Authenticity-cum-authoritymentioning
confidence: 99%
“…72 The opening of the coastal cities, however, meant that, in parallel to the Chinese "May Fourth" cultural movement (1910)(1911)(1912)(1913)(1914)(1915)(1916)(1917)(1918)(1919)(1920)(1921)(1922)(1923)(1924)(1925), eastern Hui intellectuals were quick to launch their own cultural revival movement. 73 Central to these Hui intellectuals' initiatives was the revival of their depressed Islamic learning and the education of their fellow Muslims in the ideas of modern statehood and scientific knowledge. From the year 1900 on, elite Hui Muslim families had been sending their children to Japan, an effort culminating in the establishment of the Association for Islamic Education in Tokyo (留東清真教育總會 Liudong qingzhen jiaoyu zonghui) in June 1907.…”
Section: Homogenizing Drives Of Eastern Hui: Authenticity-cum-authoritymentioning
confidence: 99%
“…Two major ethnic groups are Hui and Uygur. Many recent studies have revealed the Chinese Muslims' active participation in the national salvation movements against the Japanese invasion (J. T. Chen, 2014;Mao, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…61. For the best overview in English of this community and its relationship with the other ethnic groups in Lhasa, see Yeh, "Living Together in Lhasa"; Ma Jianye, "Xizang Lasa de Huimin, " 5:13b-16b; Yiwu, "Xizang Huimin, " 12 113. Chen Bo, "Lasa Musilin junti diaocha, " Xibei minzu yanjiu, 1, 2000: 89.…”
mentioning
confidence: 99%